PENGARUH MOTIVASI BELAJAR, PERILAKU BELAJAR, DAN MINAT BELAJAR TERHADAP TINGKAT PEMAHAMAN AKUNTANSI PADA MAHASISWA DI KOTA BATAM - venna, Riah; Tobing, Vargo Christian L. (LPPM Universitas Putera Batam, 2024)
This research examines the influence of learning motivation, learning behavior, and learning interest on the level of accounting comprehension at Universitas International Batam, Universitas Universal, and Universitas Politeknik Batam. The research population consists of 3,794 students, and data collection is conducted through online questionnaires via Google Forms, using purposive sampling with the Slovin formula resulting in a sample size of 98 respondents. The questionnaire items were measured using a Likert scale, and data analysis was carried out using IBM SPSS Version 25. The analysis includes descriptive statistics, validity-reliability tests, classical assumptions, multiple linear regression, as well as partial and simultaneous hypothesis testing. The results indicated that partially, learning motivation and learning behavior did not significantly affect accounting comprehension, while learning interest had a significant partial effect on accounting comprehension. Simultaneously, all three factors collectively influenced accounting comprehension. The Adjusted R Squared of 55.8% indicates that learning motivation, behavior, and interest affect a significant portion of accounting comprehension, while 44.2% is influenced by other factors.